Potential Application of Porous Oxide Ceramics and Composites in Concentrated Solar Technologies - Gözde Alkan; Peter Mechnich; Ferdinand Flucht; Christian Willsch (Advanced Energy & Sustainability Research)
Concentrated solar thermal technology (CST) using solid particles as integrated thermal absorptance, transport, and storage medium offers higher storage densities and lower storage costs. In this application, ceramic particles are heated up rapidly in solar receivers up to 1000 °C and carried to the heat exchanger to generate hot air or steam. Hot and cold storage containers are used to store particles and transport tubes are needed to ensure the transportation of the hot and cold particles between CST plant components. There are various material properties needed to be fulfilled by these various CST components. High mechanical stability at elevated temperatures (>1000 °C), structural and mechanical stability after long time exposure to the heat, abrasion resistance against particle collisions, thermal shock resistance, chemical stability against particles are some of the most important properties. In this study, sintered bauxite particles, (Al2O3) matrix/(Al2O3) fiber, mullite matrix/mullite fiber ceramic matrix composites, plasma‐sprayed alumina, and mullite ceramics are evaluated in terms of their mechanical properties and CST‐related functional properties. Considering all properties, possible application as CST plant components are discussed and suggested.